Potential impact of microplastics on human health: research progress - Yanbin PAN; Jianlong YAN; Shaohong DONG (Editorial Office of Chinese Journal of Public Health, 2023)
Microplastic pollution is a growing ecological problem and human exposure to micrioplastic through dietary intake, air inhalation and skin-to-skin contact is inevitable. This study provides an overview on the properties of microplastics, the pathways of microplastic exposure in humans, and potential impact of microplastics on human body systems as a reference to future research.